Gate Fees: The Pervasive Effect of IPO Restrictions on Chinese Equity Markets - Lee, Charles M C; Qu, Yuanyu; Shen, Tao (Review of Finance, 2023)
From 2007 to 2020, unlisted Chinese firms paid an average of over US $500 million to listed firms for their shell value in reverse merger transactions. We show that this large shadow price for a public listing sheds light on other features of Chinese markets, including (i) near-zero mortality rates, (ii) frequent major-asset restructurings (MARs), (iii) insensitivity of small-firm prices to corporate earnings, and (iv) a large size effect. A firm-level measure of expected shell probability (ESP) predicts stock returns, MARs, earnings-to-price sensitivity, and short-window returns to initial public offering-related regulatory news. Furthermore, adding ESP to existing pricing models for Chinese stocks significantly improves model performance.